Group dialects in an online community - VOGEL, CARL (My University, 2007)
Variations in group sub-languages evolve quickly and are a key marker of social boundaries such as those between professions, workgroups, tribes and families. In this paper we present a quantitative analysis of the effects of group structure on language use in naturalistic interaction. The data come from text chat interactions in an online social community. Using statistical techniques developed for the analysis of authorship attribution we use this corpus to test three accounts of the emergence of group sub-languages: a) local coordination mechanisms b) network topology and c) influential individuals. The results indicate that it is influential individuals who have the strongest effects on sublanguage convergence.
PUBLISHED
Keywords: Computer Science